Michael Wong Pakshong [Singapore, Managing Director of MAS] - Pakshong, Michael Wong (Institutional Knowledge at Singapore Management University, 2015)
Michael Wong Pakshong was the first Managing Director of the Monetary Authority of Singapore. He shares with DNA the challenges of building up a new institution in a newly independent country, as well as the obstacles he faced when the government's vision for MAS changed.